The Co-operative Movement in Nebraska - Weseen, Maurice H. (Journal of Political Economy, 1920)
"Cut out the middleman." Thus runs the slogan adopted by a conference of representatives of farm and labor organizations held in Chicago a few weeks ago. Perhaps no one of the many suggestions for reducing the high cost of living is more popular or more prevalent at the present moment than this one which recommends the elimination of the middleman. The American Farm Bureau Federation, a national organization with executive committee members from Massachusetts to Calitfornia, charges that the high prices paid by the consumer are altogether disproportionate to the prices received by the producer and that the middleman is the guilty party. Believing that it is hopeless to wait for governmental relief from "the merciless exploitation to which they are now subjected by the profiteers," the Plumb Plan League called an all-American farmer and labor co-operative commission to meet in Chicago February 12, 1920. At this meeting several hundred delegates from farmer organizations and various branches of the American Federation of Labor sought to institute a plan for direct dealing between farm producers and city consumers. The United States Council of National Defense, composed of the Secretaries of War, Navy, Interior, Agriculture, Commerce, and Labor, having made a careful investigation of the high-cost-of-living problem, recently reported to the public its findings and the remedies needed. The idea of co-operation is conspicuous in all of the proposals.